PENDIDIKAN AGAMA TERHADAP PENGAWASAN IBADAH SHALAT SISWA DI MTS NURUL IMAN TANJUNG MORAWA PASAR XIII DESA LIMAU MANIS T.A 2021/2022 - Nurhaizan Sembiring, Fadhillah Fikani, Tuti Alawiyah, (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
This research is motivated by the extent to which religious education influences the supervision of students' prayers at MTs Nurul Iman Tanjung Morawa Pasar XIII, Limau Manis Village, which can later influence and improve the academic achievement of students at MTs Nurul Iman Tanjung Morawa Pasar XIII, Limau Manis Village. Because one of the supervisions in the implementation of Islamic religious education is to provide prayer report books. In this case, it is intended to stimulate students in understanding the basic knowledge of religion to form aspects of faith and worship of students in particular. This study aims to clearly determine the supervision of prayer services for students in cultivating religious attitudes through religious education at MTs Nurul Iman Tanjung Morawa Pasar XIII, Limau Manis Village. The population in this study were all students at MTs Nurul Iman Tanjung Morawa Pasar XIII, Limau Manis Village, totaling 230 students. From the population, a sample of 20% of the population of 46 students was determined using a random sampling technique. Research data were collected through questionnaires and analyzed using descriptive and correlational analysis techniques using the formula r Product Moment Correlation. Based on the results of data analysis, the results of the study showed that: Implementation of Student Prayers at MTs Nurul Iman Tanjung Morawa Pasar XII Limau Manis Village with Supervision of Prayers at Mts Nurul Iman Tanjung Morawa Pasar XII Limau Manister Village classified into category B (good) with an average score of average 72.7. The Role of Religious Education in Supervision of Prayer Worship at MTs Nurul Iman Tanjung Morawa Pasar XII Limau Manis Village, based on the results of the correlation test, is significant at the 5% level of confidence, rcount rtable (0.479 0.291) is categorized as a rather low relationship. This means that the religious education of students at MTs Nurul Iman Tanjung Morawa Pasar XII in Limau Manis Village is 30% and shows that only 70% of the supervision of student prayers is influenced by other factors.